Assessing the impact of religion and family in shaping UAE national women’s choice of, and engagement with their careers - Hussain, Nazia (Cranfield University, 2015)
National women in the Gulf Cooperative Council (GCC) countries are highly educated yet their work participation remains low when compared to the rest of the world. This thesis aims to assess the impact of religion and family in the shaping of national women’s careers in the GCC workforce, in particular the United Arab Emirates (UAE). This aim is fulfilled by conducting three interlinked research projects; a systematic literature review, a qualitative study and finally, a quantitative study. The first research project comprises a systematic review of the literature that identifies the barriers and enablers to the participation and advancement of female national managers in the GCC workforce. The synthesis of articles reveals findings at the societal, organizational, family and individual levels. At the societal level, barriers and enablers are identified as those influenced by socio-cultural and religious norms and practices. These norms and practices influence how organizations (public and private) engage with their employees, and families engage with their individual members. In the second research project, I choose to narrow the scope of my research from six GCC countries to one country, the UAE. I explore the influence of family on the experiences of ten senior female UAE national managers at key work decision stages; I employ semi-structured interviews and, based on their experiences, the findings reveal that the family has influence at both the role entry and role participation stages. No data were available for the role exit stage. Furthermore, the experiences are different for women from extended versus nuclear families. In the third research project I choose to focus on the factors that support and impact on the experiences of UAE national women during their career life cycle. The findings indicate that overall there are no differences between the experiences of women from nuclear families versus extended; however, there are differences between the model and the UAE sample, both at the overall level and individual age stages. My second research project; a qualitative study provides three contributions to knowledge. Firstly, I extend the understanding of work related decisions, taking into account family influences. However, in the UAE, based on my research, the outcome will primarily be in favour of family due to the influence of socio-cultural and religious norms and practices. I propose that the conceptual framework be extended by adding the component of religion to it when considering the context of the UAE. Secondly, I propose a modification to the framework enabling it to be used in the UAE context. Thirdly, no previous empirical research has been conducted using this framework, with the result that the data from my research contribute empirically. With respect to contribution to practice, this qualitative study identifies the need for enhanced recruitment strategies for women and more gender friendly policies and practices to ensure the effectiveness of Emiratization within both the public and private sectors. The evidence from my third research project; a quantitative study contributes theoretically as my research demonstrates that the O’Neil and Bilimoria (2005) three phase women’s career development model does not fit in the UAE context. The research also contributes from a practical perspective as it identifies the need to improve the development of networking, communication and leadership skills for women and the implementation of comprehensive flexible working practices for women.
Keywords: Career development; Family influence; Religion; Culture; Arab Middle East